PENGARUH EQUITY TO TOTAL ASSET RATIO (EAR), LOAN ASSET RATIO (LAR), CAPITAL ADEQUENCY RATIO (CAR), NON PERFORMING LOAN (NPL), DAN LOAN DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA) (Pada Perusahaan Perbankan Periode 2009-2013) - Anik Wahyuningsih, 11.05.52.0041; Aini, Nur (Students Journal of Accounting and Banking, 2015)
The study examines the effect of EAR, LAR, CAR, NPL, and LDR to ROA. This research was conducted at the Indonesian Stock Exchange by using a go public banking company as the unit analysis. The sampling method used purposive sampling with the observation period from 2009 to 2013. Relationship and (or) influence between variable is described by using multiple regression analysis. Result of this research show that simultancy independent variables EAR, LAR, CAR, NPL, and LDR have significant influent to ROA. While, partially EAR and LDR have positive influent and significant to ROA. Evenwhile LAR, CAR, and NPL has negatif influent and significant to ROA.Keywords: Equity to Total Asset Ratio, Loan Asset Ratio, Capital Adequacy Ratio, Non Performing Loan, Loan to Deposit Ratio, Return On Asset